2005
DOI: 10.1111/j.1601-5223.2004.01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inheritance to leaf rust in wheat using area under disease progress curve

Abstract: Six varieties, Kundan (K), Galvez-87 (G), Trap (T), Chris (C), Mango (M) and PBW-348 (P) along with fast ruster, Agra Local (AL), were screened for seedling reaction and adult pant response to leaf rust. Seedlings of all six varieties were susceptible while adult plants showed lower susceptability response than Agra Local. The F1s among the varieties, and also with Agra Local, showed the values lesser than the respective mid parental values for AUDPC suggesting a polygenic mode of inheritance. ANOVA for combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…This indicated the involvement of additive and non-additive gene actions in determining the inheritance of the studied characters. Results of this study were in accordance with the findings of Ahamed et al (2004), Kumar et al (2011) and Fellahi et al (2013), who reported significant differences for both GCA and SCA for these traits. The components of variance indicated more GCA variance (1051.82) than SCA variance (139.45) for AUDPC of stem rust (Table 4).…”
Section: Combining Ability Analysissupporting
confidence: 95%
See 2 more Smart Citations
“…This indicated the involvement of additive and non-additive gene actions in determining the inheritance of the studied characters. Results of this study were in accordance with the findings of Ahamed et al (2004), Kumar et al (2011) and Fellahi et al (2013), who reported significant differences for both GCA and SCA for these traits. The components of variance indicated more GCA variance (1051.82) than SCA variance (139.45) for AUDPC of stem rust (Table 4).…”
Section: Combining Ability Analysissupporting
confidence: 95%
“…This indicated the partial dominant nature of stem rust resistance in these crosses. Different levels of intermediate disease reactions in most of the slow ruster 9 slow ruster and slow ruster 9 susceptible crosses were observed, suggesting a polygenic mode of inheritance of rust resistance (Ahamed et al 2004;Irfaq et al 2009). The AUDPC value of 625.0 in fast ruster 9 fast ruster was higher than the AUDPC value of 582.0 in its susceptible parent.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this case, however, the additive 9 dominance interaction [j] is negative, which indicates that the gene interaction may be considered duplicated (Mather and Jinks 1977). This duplicate epistasis may have a small role in selection as it decreases the effect of heterosis in selection (Lal-Ahamed et al 2004), and it also points to the presence of resistance factors in the susceptible parent.…”
Section: Discussionmentioning
confidence: 98%
“…The csLV34a allele (229 bp) was detected in the check cultivar Giza 139 and csLV34b allele (150 bp) was detected in the near isogenic line Thatcher Lr 34 (Figure 1 of AUDPC (up to 840). Consequently, these varieties classified as the highly susceptible or fast rusting varieties group [25] found that the wheat cultivar Agra Local showed the highest value of AUDPC (1300), the wheat cultivar Kundan showed least AUDPC value (217). While the wheat cultivars Trap (317), Galvez-78 (344), Mango (412), Chris (504) and PBW-348 (737) [26] reported that the wheat cultivars Chenab 70, WL 711, Pak.…”
Section: Discussionmentioning
confidence: 99%